Standard Costing System - a management tool by deviations - Simeonova, R. (Економічний вісник Донбасу, 2016)
Standard Costing System nowadays serves as a reliable tool to control and manage production costs. This article studies the theoretical and practical-applied aspects related to its use. The different types of standard cost are examined and a model for applying it is developed. Particular attention is paid to the deviations in the Standard Costing System, and these are classified according to their nature. Formulas for analysis of the deviations are proposed. Their application is illustrated with suitable examples. The importance of standard prices and some difficulties relating to their use is shown. У сучасних умовах системи Standard costing служать надійним інструментом контролю та управління виробничими витратами. У цій статті аналізуються теоретичні та практико-прикладні аспекти, пов'язані з їх використанням. Розглянуто різні різновиди стандартної собівартості. Розроблена зразкова модель для її застосування. Особлива увага приділяється відхиленням у системі Standard costing, які також були систематизовані залежно від їх природи. Запропоновано формульний апарат для аналізу відхилень. Його застосування ілюструється відповідними прикладами. Зазначено призначення стандартної ціни і деякі труднощі, що стосуються їх використання. В современных условиях системы Standard costing служат надежным инструментом контроля и управления производственными затратами. В настоящей статье анализируются теоретические и практико-прикладные аспекты, связанные с их использованием. Рассмотрены различные разновидности стандартной себестоимости. Разработана примерная модель для ее применения. Особое внимание уделяется отклонениям в системе Standard costing, которые также были систематизированы в зависимости от их природы. Предложен формульный аппарат для анализа отклонений. Его применение иллюстрируется соответствующими примерами. Указано назначение стандартной цены и некоторые трудности, касающиеся их использования.